No evidence of pulmonary hypertension revealed in an echographic evaluation of right-sided hemodynamics in hyperthyroid cats. Issue 12 (December 2022) - Lachance, Laury; Conversy, Bérénice; Wiggen, Kelly; Pavard, Christophe; Reinero, Carol; Masseau, Isabelle
Objectives: Hyperthyroidism is a common endocrinopathy affecting middle-aged to elderly cats, with multisystemic repercussions. Hyperthyroid humans show decreased lung compliance and increased cardiac output with subsequent left heart failure leading to pulmonary capillary congestion. Prognosis worsens with the development of increased pulmonary vascular pressures (ie, pulmonary hypertension [PH]) in hyperthyroid humans. The effect of excess thyroid hormone concentration on pulmonary arterial hemodynamics is unknown in cats. Assessing pulmonary vascular pressures in veterinary medicine relies heavily on echocardiographic measurements performed at the level of the heart and pulmonary trunk. This study investigated right-sided cardiac and pulmonary arterial hemodynamics in hyperthyroid cats using echocardiography. Methods: Echocardiographic examinations of hyperthyroid cats identified through a bi-institutional database search were reviewed for the determination of systolic pulmonary arterial pressure (PAP) and 20 other metrics. Values were compared with those of a healthy cat group using non-parametric statistical analyses. Results: Systolic PAP could not be determined in 23/26 hyperthyroid and 13/14 healthy cats owing to unmeasurable tricuspid regurgitation flow velocity. Hyperthyroid cats were roughly twice as old ( P <0.001) and had 2–4-fold higher respiratory rates ( P <0.001) than healthy cats. Hyperthyroid cats showed an increase in acceleration time-to-ejection time ratio of pulmonary flow (1.4-fold, P  = 0.001), pulmonary artery velocity time integral (1.2–1.6-fold, P  = 0.001), maximal pulmonary velocity (1.3–1.7-fold, P  = 0.002), stroke volume (1.5-fold, P  = 0.001) and cardiac output (1.6-fold, P <0.001) vs healthy cats. None of the other echocardiographic metrics reached statistical significance. Conclusions and relevance: Systolic PAP estimation proved unsuitable as a sole measurement for the assessment of PH in hyperthyroid cats owing to the frequent inability to interrogate tricuspid regurgitant flow velocity. Hyperthyroid cats have altered echocardiographic measures of pulmonary hemodynamics dissimilar to those reported in hyperthyroid humans. Differential effects of thyrotoxic cardiomyopathy on ventricular systolic function may underlie species differences.